A causa dos contratos - Bechara, Guilherme Fontes (2014)
This paper has the purpose of analyzing the cause of contracts. The subject is relevant and justifiable because although there is no statutory provision on the cause of contracts, it is important to the theory of contracts. Moreover, its practical importance is unquestionable. It is herein inquired what is the concept of the cause of contracts and what is the role played by it in the national legal system. Through academic research carried out in domestic and foreign doctrine and case law of Brazilian Courts, particularly the Superior Court of Justice and Court of Appeals of the State of São Paulo, this paper concludes that the cause of contracts are the practical intent of the contract which is highlighted by the parties comprised in the contractual provisions. It is also argued the relevance and practical application of the concept of cause of contracts in several areas of law notably the ones related to the interpretation and classification of contracts and in situations involving the issues of contractually linked agreements (contratos coligados), general duty of good faith, social role of the agreement and frustration. Finally, it is emphasized the large number of legal opinions where the cause of contracts have directly or indirectly driven the decision of the case